2015
DOI: 10.1039/c5ra04168f
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen diffusion in MgH2 doped with Ti, Mn and Fe

Abstract: Incorporation of suitable dopants in MgH2 is widely investigated as the way of improving hydrogen storage characteristics of this material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…Pozzo and Alfe suggested that Fe‐doped Mg surface reduces the activation barrier for the diffusion of hydrogen significantly. In contrast, Koteski et al . have suggested that the migration of hydrogen may be hindered by Fe‐substituted Mg surfaces in the MgH 2 system.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Pozzo and Alfe suggested that Fe‐doped Mg surface reduces the activation barrier for the diffusion of hydrogen significantly. In contrast, Koteski et al . have suggested that the migration of hydrogen may be hindered by Fe‐substituted Mg surfaces in the MgH 2 system.…”
Section: Introductionmentioning
confidence: 92%
“…In such ac ase, the performance of the system was shown to be highly dependento nt he diffusion of hydrogen across the Fedoped surface. Pozzo and Alfe [19] suggestedt hat Fe-doped Mg surfacer educes the activation barrierf or the diffusion of hydrogen significantly.I nc ontrast, Koteski et al [20] have suggested that the migration of hydrogen may be hindered by Fe-sub-stitutedM gs urfaces in the MgH 2 system. Hussain et al [21] have suggested that Fe atoms, when substituted in the MgH 2 lattice, make al ocal deformationb yr earranging the Mg and Hp osition in its vicinity andt hereby reducing the MgÀHb ond strength.R ecent investigation of Dai et al [22] employing Al,T i, Mn andN is uggested that the chemical role of each of these dopantsi sc onsiderably different for improving the performance of MgH 2 .K eeping theser esults in view,w eh ave focused to find out what chemical changest he employed additive undergo during the dehydrogenation of MgH 2 ,w hich can possibly give clues for understanding the role of additive for MgH 2 system.…”
Section: Introductionmentioning
confidence: 99%
“…Improvement of the hydrogen absorption/desorption kinetics is achieved through shortening the path for H diffusion (nanostructures, thin films) or by introducing appropriate dopants which act as catalysts. , In the last years, research has focused on the use of transition metals (TM) as dopants. TMs are considered good candidates to change the hydrogen diffusion kinetics and the stability of MgH 2 . , The TM influences the stability of the MgH 2 and causes weakening of the Mg–H bonds. Consequently, TM doping leads to a variation of the cell volume.…”
Section: Introductionmentioning
confidence: 99%
“…Among the long list of catalysts or additives used to enhance the poor hydrogenation/dehydrogenation behaviors of MgH 2 powders, Ti metal is one of the best catalytic agents used to enhance the absorption and desorption kinetics of MgH 2 . 20,21 Like other MgH 2 -based systems, catalyzing of MgH 2 powder by Ti is usually carried out by “manual” doping of the powder with the desired weight percentage of Ti particles/nanoparticles and then mechanically ball-milling them for a certain time, which can extend to several hours. 21 A major drawback of this traditional approach is the long milling time required to ensure uniform dispersion of Ti into the MgH 2 matrix.…”
Section: Discussionmentioning
confidence: 99%